Improving Trend of Adhering to Ethical Measures in Iranian Research in Human Genetics: A Survey from 2005 to 2009; and the Road Ahead. - Seyed Hasan Saadat; Khodabakhsh Ahmadi; Fakhruddin Feyzi; Mostafa Ghanei (Tehran University of Medical Sciences, 2013)
The overwhelming rate of progress in biotechnological research especially in human genetics, as well as the high levels of power these researches provide us to intervene in human lives, brings serious concerns on the ethical problems that may rise from these research endeavors. To address this critical issue in Iran, we conducted a study issuing publishing authors of studies in human genetics from Iran, between years 2005 to 2011.We contacted 116 corresponding authors of articles issuing genetics research on human subjects, asking them that whether they have gotten either informed consent from their study subjects or ethical approval from their institutional ethics committee.Only 13% of the authors presented both documents; 52% had not gotten any of the documents; 19% of authors felt no need for getting the mentioned documents; 13% declared that they only gotten oral consent and 3% of authors did not remember whether they have gotten any documentation or not.The trend for informed consent taking was improving over time, from 5% in year 2006 to 24% in 2009. The result was not satisfactory but showed good trend towards improvement, recommending more serious follow up concerning ethical aspects of articles published in human genetics.